Introduction - Pierre Chastang (Tabularia)
The object of this study is, on the basis of some important publications concerning cartularies, to retrace both the various steps of the emergence of a historiographical field devoted to culture and to writing practices and the links that it has established with the other fields focusing on erudite writing, amongst which diplomacy comes first. We will then examine what is at stake in writing up a cartulary and we will do so starting from three notions: archiving, representing and governing. After this, once the demands stemming from the renewed questioning of historians and diplomatists are specified, we will deal with the question of the census and with the publication of codices.